Analisis Penerapan Lean Six Sigma dalam Peningkatan Kualitas Pelayanan di Rumah Sakit - Endah Pravita Putri Aldia Pratama; Safinah Annajah; Khansa Adristi; Acim Heri Iswanto (Jurnal Ventilator, 2023)
The quality of hospital services will affect patient satisfaction and also their loyalty in using these facilities and the rapid development of health services currently requires hospital managers to run their business well. in the hospital. This study uses the method of literature review (literature review) with search engines used in literature searches including Google Scholar and Research gate with the keywords Service Quality Improvement, Lean Six Sigma, Hospitals. The resulting articles were selected based on publications published between 2018 and 2023. The results showed that the application of lean six sigma in hospitals in improving the quality of their services can be carried out through the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The conclusions of this study indicate that the application of lean six sigma can reduce difficulties, increase speed, and separate activities that have added value or value added from activities that have no added value or non-value added in hospitals, such as improving service quality by setting priorities by according to the highest gap required by the patient.